Covid-19: Online Education and Its Challenges to Parents of Primary School Children in Aluva Taluk - et. al., Rehna John M, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The introduction of online learning has presented a lot of challenges for many children and added an extra layer of stress for parents. Most of them may additionally be undergoing stress related to finance, employment and household work. This study is conducted among the parents of primary school children to understand their challenges in online education and how difficult it is for them to manage their job and household works in the scenario of Covid’19 pandemic. The data has been collected from 200 parents of Aluva Taluk. The study brings out the challenges such as technical issues, stress, time management issues and issues as a result of concern towards their child. The analysis was carried out with the SPSS software utilizing various statistical tools. It is found that the online education is a real challenge for the parents of primary school children.